AGGRESSIVE BEHAVIOR THROUGHOUT LIFETIME - Rasulova Feruza Fayzullaevna (Galaxy International Interdisciplinary Research Journal, 2023)
Throughout the lifespan, aggressive conduct can appear, from attention-deficit hyperactivity disorder (ADHD) in children and adolescents to domestic violence in adults. Aggressive behavior is a sign of many psychiatric diseases. While a large portion of the study on aggressiveness has been on adolescents and adults, less focus has been placed on understanding the origins of violent behaviors across the entire developmental spectrum. This study aims to provide an overview of the presentation and causes of aggressive behavior across the life span. The potential repercussions for both the aggressors and the victims are also described. The psychosocial literature has extensively investigated several aspects of aggressiveness, including adult aggression and violence, psychopathology, adult aggression and criminal conduct, and adolescent aggression and developmental theories. This paper aims to provide a fundamental overview of aggressive behavior and its presentation and risk factors in significant age groups. By doing this, we offer a framework for predicting, addressing, and stopping aggressive behavior across the age span.